Outcome Measures Following Critical Illness in Children With Disabilities: A Scoping Review - Julia A. Heneghan; Sarah A. Sobotka; Madhura Hallman; Neethi Pinto; Elizabeth Y. Killien; Kathryn Palumbo; Sinead Murphy Salem; Kilby Mann; Barbara Smith; Rebecca Steuart; Manzilat Akande; Robert J. Graham (Frontiers Media S.A., 2021)
Children with disabilities compose a substantial portion of admissions and bed-days in the pediatric intensive care unit (PICU) and often experience readmissions over time. Impacts of a PICU admission on post-discharge health status may be difficult to distinguish from pre-existing disability in this population. Efforts to standardize outcome measures used for children with disabilities may help identify morbidities associated with PICU hospitalizations. Although a scoping review of outcome measures to assess children after episodes of critical illness has recently been published, it is not known to what extent these measures are appropriate for use in children with disabilities. This limits our ability to effectively measure long-term outcomes following critical illness in this important patient population. Through mixed methodology of scoping review and multi-stakeholder consensus, we aimed to identify and describe instruments previously utilized for this purpose and to explore additional tools for consideration. This yielded 51 measures across a variety of domains that have been utilized in the PICU setting and may be appropriate for use in children with disabilities. We describe characteristics of these instruments, including the type of developmental domains assessed, availability of population data, validation and considerations regarding administration in children with disabilities, and ease of availability of the instrument to researchers. Additionally, we suggest needed alterations or accommodations for these instruments to augment their utility in these populations, and highlight areas for future instrument development.